RANCANG BANGUN ALAT PENGATURAN ARAH PUTAR MOTOR DC POWER WINDOWS BERBASIS PLC PANASONIC MENGGUNAKAN HUMAN MACHINE INTERFACE (HMI) - Alfitri, Tafki Aunika Fariz; Setiono, Iman (Gema Teknologi, 2017)
Tafki Aunika Fariz Alfitri, Iman Setiono, in this paper explain that at this time human life has become more advanced especially in the field of science and technology, all people compete to create technology that is useful and easy for humans. At present the equipment in general has used a remote monitoring and operation system. This system usually uses a microcontroller or PLC as a control. In an effort to facilitate human work, in this case I tried to make a design setting the direction of rotation of the DC power windows. This DC power windows motor is usually used in the car to move the windshield up and down. This Windows power DC motor uses a power supply of 12 volt DC and the output is between 0-5 Volt. This design uses Panasonic PLC as its main control. By using the relay as a reverse rotation setting and forward DC power windows, the motor will automatically move in reverse and forward. The input of a 24 Volt DC panasonic PLC originating from the adapter. The design of this tool can later be applied to a glass in the car by using the Panasonic PLC as its control and other component components needed in the design of the rotary direction arrangement. In the operation by way of toch screen using a human machine interface as a contruction tool to drive the DC power window to spin in reverse or forward.